Local Structure of Europium‐Doped Luminescent Strontium Fluoride Nanoparticles: Comparative X‐ray Absorption Spectroscopy and Diffraction Study. Issue 11 (12th September 2021) - Yusenko, Kirill V.; Kabelitz, Anke; Schökel, Alexander; Wagner, Ralph; Prinz, Carsten; Kemnitz, Erhard; Emmerling, Franziska; Krahl, Thoralf; Guilherme Buzanich, Ana
Abstract: Rare‐earth based luminescent materials are key functional components for the rational design of light‐conversion smart devices. Stable Eu 3+ ‐doped strontium fluoride (SrF2 ) nanoparticles were prepared at room temperature in ethylene glycol. Their luminescence depends on the Eu content and changes after heat treatment. The crystallinity of heat‐treated material increases in comparison with as‐synthesized samples. Particles were investigated in solution using X‐ray diffraction, small‐angle X‐ray scattering, and X‐ray spectroscopy. After heat treatment, the size of the disordered nanoparticles increases together with a change of their local structure. Interstitial fluoride ions can be localized near Eu 3+ ions. Therefore, non‐radiative relaxation from other mechanisms is decreased. Knowledge about the cation distribution is key information for understanding the luminescence properties of any material. Abstract : Extended X‐ray fine structure (EXAFS) spectroscopy studies supported by wide and small X‐ray scattering data give comprehensive insights into the local structure of luminescent SrF2 doped by EuF3 . Eu surrounding does not change considerably with increasing Eu content. Each Eu 3+ position has 1–1.7 interstitial F atom (Fi ). Heating does not change Eu's occupancy in the crystal structure.